AN ESSAY ON GUIRGIS’S PLAY THE LAST DAYS OF JUDAS ISCARIOT - MALABA KOMPANYA, Pierre (International Journal of Scientific Research and Management (IJSRM), 2022)
The Last Days of Judas Iscariot is a tremendous modernist play of new ideas that the writer has communicatively addressed to his contemporaries with the aim of turning a biblical account of Judas Iscariot’s betrayal of Jesus of Nazareth into a trial where he has brought in judges, lawyers, and witnesses.However, Guirgis has attempted to question and break the traditions, to question the established truths, certainties, ideas while seeking after new ones. Such new truth as heaving Judas Iscariot on the stand before judges, lawyers, and witnesses with the purpose to examine his case.